The effect of Lactobacillus fermentum DALI02 in reducing the oxidative stress and inflammatory response induced by high-fat diet of rats. Issue 57 (16th September 2020) - Huang, Yujun; Qu, Hengxian; Liu, Dong; Wa, Yunchao; Sang, Jian; Yin, Boxin; Chen, Dawei; Chen, Xia; Gu, Ruixia
Abstract : A long-term high-fat diet (HFD) leads to significant oxidative stress in the body and induces inflammation. Abstract : A long-term high-fat diet (HFD) leads to significant oxidative stress in the body and induces inflammation. A preliminary evidence suggests a potential therapeutic utility of probiotics for this condition. To evaluate the potential effect of Lactobacillus fermentum DALI02 on the oxidative stress and inflammatory damage induced by HFD, we used a hyperlipidemic rat as a model fed with HFD. Results revealed that HFD induced a significant oxidative stress and inflammation. However, results reveal that L. fermentum DALI02, manifested a significant decrease in levels of malondialdehyde (MDA), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and resistin, while the catalase (CAT), total antioxidant capability (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and adiponectin (ADPN) levels significantly increased. And it was dose-dependent that the effect of high dose groups with high viable count was particularly notable. The results suggest that L. fermentum DALI02 could alleviate oxidative stress and inflammation as it appeared to reduce lipid peroxidation and improved the lipid metabolism in vivo .